Influence of Dietary Mannan-oligosaccharide and ï¡-Tocopherol on Intestinal Microbiology and Histomorphology in Broiler Chickens - Sinha, Pallavi; Kumar, Sanjay; Kumar, Kaushalendra; ., Chandramoni; Sinha, Manju; Kumar, Deepak; Kumari, Rajni; Kumari, Sushma (Indian Journal of Animal Nutrition, 2019)
Day-old Vencobb broiler chicks (240) were randomly assigned to 4 dietary treatment groups having 3 replicates of 20 birds each to study the effect of mannan oligosaccharide (MOS) and Î±-tocopherol on intestinal microbiology and histomorphology. The trial lasted for 7 weeks. The chicks were fed with standard basal diet. The control group T1 was fed a basaldiet. The birds in group T2 were fed control diet as in T1 + Î±-tocopherol @ 400IU per kg of feed; in group T3: control diet as in T1 + mannan-oligosaccharide @ 0.4% and in group T4: control diet as in T1 +Î±-tocopherol @ 400IU per kg feed + mannan-oligosaccharide @ 0.4% in feed, respectively. The results of study revealed that supplementation of MOS and AT in the diet of birds showed significant (P<0.05) lowering in cfu count of pathogenic bacteria as E.coli and Salmonella spp. as compared to the control group. The effect on the histomorphology of the birds also showed a significant (P<0.05) increase in the villi height (VH) and surface area (SA) of different parts of the intestine on supplementing the feed with MOS and AT. Thus, it was concluded that supplementation of MOS and AT improves the gut health and also had a positive influence on the microarchitecture and integrity of the intestine.